2020
DOI: 10.1038/s41598-020-68744-2
|View full text |Cite
|
Sign up to set email alerts
|

Optical phonons of SnSe(1−x)Sx layered semiconductor alloys

Abstract: The evolution of the optical phonons in layered semiconductor alloys SnSe(1-x)Sx is studied as a function of the composition by using polarized Raman spectroscopy with six different excitation wavelengths (784.8, 632.8, 532, 514.5, 488, and 441.6 nm). The polarization dependences of the phonon modes are compared with transmission electron diffraction measurements to determine the crystallographic orientation of the samples. Some of the Raman modes show significant variation in their polarization behavior depen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 43 publications
(90 reference statements)
3
29
0
Order By: Relevance
“…Due to the observed behavior of different peaks, we can assume that (i) the polarization properties of the B 2 1g mode can be used to determine the crystallographic axes in GeS, but without attribution the zigzag and armchair directions; (ii) the variation of the polarization axis of the A 3 g as a function of the excitation energy suggests that the electron-phonon coupling may change the A 3 g polarization axis (see the work in [32] for details); and (iii) due to 2-fold symmetries of the polarization properties (except for 1.96 eV) and the almost fixed polarization axis of the A 4 g mode, its polarization properties are good to identify the zigzag and armchair crystallographic directions. Note that the observed influence of the excitation energies on the axes and shape of polarization properties of phonon modes is very similar to those reported for different anisotropic layered materials, e.g., BP, ReS 2 , ReSe 2 , SnSe 1−x S x [6,9,[32][33][34]. Moreover, as the effect of thickness on the polarization properties of different modes in BP has been reported [6,33], the outline of further research on thin layers of GeS seems to be clear.…”
Section: Vibrational Propertiessupporting
confidence: 81%
“…Due to the observed behavior of different peaks, we can assume that (i) the polarization properties of the B 2 1g mode can be used to determine the crystallographic axes in GeS, but without attribution the zigzag and armchair directions; (ii) the variation of the polarization axis of the A 3 g as a function of the excitation energy suggests that the electron-phonon coupling may change the A 3 g polarization axis (see the work in [32] for details); and (iii) due to 2-fold symmetries of the polarization properties (except for 1.96 eV) and the almost fixed polarization axis of the A 4 g mode, its polarization properties are good to identify the zigzag and armchair crystallographic directions. Note that the observed influence of the excitation energies on the axes and shape of polarization properties of phonon modes is very similar to those reported for different anisotropic layered materials, e.g., BP, ReS 2 , ReSe 2 , SnSe 1−x S x [6,9,[32][33][34]. Moreover, as the effect of thickness on the polarization properties of different modes in BP has been reported [6,33], the outline of further research on thin layers of GeS seems to be clear.…”
Section: Vibrational Propertiessupporting
confidence: 81%
“…Wen et al found the highest anisotropic mobility ratio of 5.6 for ReS 1.02 Se 0.98 , which is larger than that of ReS 2 and ReSe 2 . As for 2D SnS 1– x Se x , the synthesis, valleytronics, optoelectricity, and anisotropic optical and structural characteristics as a function of content are systematically studied in recent years by us , and other groups. It is confirmed that the polarized Raman spectrum and electrical and photoresponse time in the broadband spectrum are maintained and improved through alloying. However, in-plane anisotropic electrical and photoresponse properties of ultrathin 2D SnS 1– x Se x have rarely been reported, which also need an ultrathin rounded shape to stimulate the optimum anisotropic properties such as black phosphorus (BP), GaTe, and so on. , …”
Section: Introductionmentioning
confidence: 80%
“…The ultrathin orthorhombic SnS 0.5 Se 0.5 belongs to the D 2 h point group. Meanwhile, only A g and B 3g Raman modes can be found in the sample on the Y – Z plane (100), and their Raman tensors are given as follows ,, …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BP, ReS 2 , ReSe 2 , SnSe 1−x S x . [28][29][30][31][32] Moreover, as the effect of thickness on the polarization properties of different modes in BP has been reported, 29,30 the outline of further research on thin layers of GeS seems to be clear.…”
Section: Vibrational Propertiesmentioning
confidence: 99%